Żydło ich: mało warzonego albo pieczonego używają, czyli nazwy kulinariów i naczyń stołowych na dworze Dymitra Samozwańca I - Pihan-Kijasowa, Alicja (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2012)
Polish memoirs and diaries from the beginning of the seventeenth century provide priceless yet little known source material for linguistic research studies, including lexical studies. Within the scope of the discussed thematic field (i.e. names of dishes, beverages and tableware), the diaries provide a sizeable and diversified source material. Among the names of dishes and tableware mentioned in the excerpted diary of Stanisław Niemojewski, well-known definitions and those deeply-rooted in the tradition in the Polish language are dominant. In many instances, they belong to common lexical resources of the Polish and Russian languages, though substantially numerous foreign (Russian) borrowings do occur. The Polish guests at the Tsar’s court at the time were not capable of identifying or naming many dishes. When this was the case, they resorted to using descriptive and multi-element designations. The otherness of Russian culture, coupled with the perceivable dissimilarities in table culture, triggered evaluative and affective responses and judgments of the diarists. Thus, so many evaluative assessments of the food, more often than not negative rather that favourable. This unfavourable attitude of Polish diarists with regard to what they saw and experienced stemmed not only from objective observation but was also influenced by a difficult situation the diarists were in after their arrival in Russia. Things as they were, the beginning of the seventeenth century was marked by the tumultuous and complicated period of Russian-Polish relations.